1989
DOI: 10.1080/09595238980000121
|View full text |Cite
|
Sign up to set email alerts
|

Drinking patterns of Australian tertiary youth

Abstract: In this review Australian research on the drinking patterns, beliefs and attitudes toward alcohol of young adults undertaking tertiary education is examined. Most studies reveal that a majority of students are light to moderate drinkers. Alcohol is readily available to these young adults, and is an important component in many of their social activities. Students generally do not perceive alcohol use to be a possible health problem for themselves. For the majority this is probably true. However, many studies id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Their personal inexperience with alcohol and limited exposure to peer drinking situations [i3,I4] may explain their stronger endorsement of reasons such as getting into bad company and not knowing enough about what alcohol can do. As predicted, the mid-teen respondents and the older adolescents were very similar in their mean ratings, suggesting that increased opportunities to drink and observe alcohol consumption during the mid-teen [4] and young adult years [24] give adolescents similar perceptions about the reasons for risky or illegal consumption.…”
Section: Discussionsupporting
confidence: 55%
“…Their personal inexperience with alcohol and limited exposure to peer drinking situations [i3,I4] may explain their stronger endorsement of reasons such as getting into bad company and not knowing enough about what alcohol can do. As predicted, the mid-teen respondents and the older adolescents were very similar in their mean ratings, suggesting that increased opportunities to drink and observe alcohol consumption during the mid-teen [4] and young adult years [24] give adolescents similar perceptions about the reasons for risky or illegal consumption.…”
Section: Discussionsupporting
confidence: 55%
“…Perhaps surprisingly, given the high prevalence of hazardous drinking among tertiary students in Australasia (Kypri, Langley, McGee, Saunders, & Williams, 2002;Roche & Watt, 1999;Wilks, 1989), research on this topic is limited to one study of a convenience sample, in which 26% of Australian students reported, in the past 12 months, being under the influence of alcohol while a designated driver (Stevenson et al, 2001). That study highlighted the problems of both drink-driving and being the passenger of a drink-driver (so-called "drinkriding").…”
Section: Introductionmentioning
confidence: 99%
“…Even though 18 23-year-olds who drink (and university students in particular) are regularly identified as being at risk and warranting special attention, comparatively little work has been undertaken to identify problems and determine appropriate solutions [10]. This is despite concerns raised by health care providers, law enforcement agents and in observational and anecdotal reports.…”
Section: Introductionmentioning
confidence: 99%